Why Are So Many Water Points in Nigeria Non-Functional? : An Empirical Analysis of Contributing Factors - Andres, Luis (World Bank, Washington, DC, 2018)
This paper utilizes information from the 2015 Nigeria National Water and Sanitation Survey to identify the extent, timing, as well as reasons for the failure of water points. The paper finds that more than 38 percent of all improved water points are nonfunctional. The results indicate that nearly 27 percent of the water points are likely to fail in the first year of construction, while nearly 40 percent are likely to fail in the long run (after 8-10 years). The paper considers the reasons behind these failures, looking at whether they can or cannot be controlled. During the first year, a water point's location -- the political region and underlying hydrogeology -- has the greatest impact on functionality. Other factors—specifically, those that can be controlled in the design, implementation, and operational stages -- also contribute significantly. As water points age, their likelihood of failure is best predicted by factors that cannot be modified, as well as by the technology used. The paper concludes that, to improve the sustainability of water points, much can be done at the design, implementation, and operational stages. Over time, technology upgrades are important.